Hambatan, Tantangan, dan Tingkat Pengetahuan Tenaga Medis dalam Penanganan Gigitan Ular: Tinjauan Literatur - Safitri, Rizki Mega; Mahyuvi, Tata; Ramadhan, Sukma Cahya (Journal of Pubnursing Sciences, 2024)
Background: Snakebites are an emergency medical condition that requires quick and precise treatment. Aim: To explores the barriers, challenges, and knowledge levels of medical workers in handling snakebites in healthcare facilities. Method: Data were collected through a literature review of selected articles. Resulth: The results of the research literature review show several major obstacles in snakebite treatment, including limited access to antivenom, lack of adequate medical facilities, and delays in handling due to the long distance from medical centers. Challenges include limited specialized training for medical personnel, lack of trained human resources, and difficulties in identifying snake types and assessing bite severity. The medical workforce's knowledge of snakebite treatment varies, with most showing a basic understanding but lacking in specific knowledge regarding optimal treatment procedures and the correct use of antivenoms. Conclution: This study highlights the importance of continuous training and increased access to medical resources to improve the effectiveness of snakebite treatment.